Psychodermatology: An evolving paradigm - Swapna Bondade; Abhineetha Hosthota; R Bindushree; P Raghul Raj (Wolters Kluwer Medknow Publications, 2022)
Psychodermatology is a specialty that highlights admix between psychiatry and dermatology. It is emerging as a new subspecialty in dermatology. The skin and central nervous systems are related through their common embryonic origin - ectoderm. They also have common neuromodulators, peptides, and biochemical systems of internal information. Psychiatry is more focused on the internal invisible symptoms, and dermatology is focused on the external visible signs. This connection between skin disease and psyche has unfortunately been underemphasized. Increased pathophysiological understanding of these issues, with biopsychosocial approaches and clinics of psychodermatology would be highly beneficial. Multicenter research such as prospective case-controlled studies and therapeutic trials about the association of skin and psyche can provide more insight into this unexplored and exciting field of medicine.